Land Management Dynamics in Social Forestry Permit Using LandTrendr Algorithm: A Case Study in Tuar Tana Community Forest, East Nusa Tenggara Province, Indonesia - Heru Budi Santoso; Wahyu Wardhana; Ronggo Sadono (Forest Science and Technology)
Social forestry is one of the Indonesian government’s programs to reduce deforestation and improve community welfare. After a decade, it is not yet known how the dynamics of land management related to the level of disturbance and recovery before and after the permit in the Tuar Tana Community Forest (HKm Tuar Tana) area in East Nusa Tenggara Province. This study aims to investigate the dynamics of land management by monitoring the level of disturbance and recovery in social forestry areas before and after the permit using the LandTrendr algorithm and the Normalized Burn Ratio (NBR) index. The results showed that the highest vegetation loss occurred before the permit was granted, 118.90 ha or 88% of the total loss area from 2000 to 2023. Vegetation recovery mostly occurred over a long duration of 22 years with an area of 25.82 ha. Based on the comparative analysis of the level of disturbance between 2000 and 2023, there was a decrease in the level of disturbance with a high level of 119.96 ha or a decrease of 34.58% of the total area of the HKm Tuar Tana permit, while the disturbance with a moderate level increased by 117.90 ha or 33.9%. This condition shows that over time, there has been a change in land clearing patterns in the HKm Tuar Tana, from massive land clearing by cutting and burning to selective land clearing adjusted to the growth of non-timber forest products planted in the previous year. In line with the research findings, LandTrendr can be a highly relevant tool for evaluating the impact of social forestry policies on vegetation cover in a quantitative and evidence-based manner. The recommendation is that the government should strengthen this program’s implementation by providing technical assistance and continuous supervision to communities regarding land management in social forestry areas. This is important to ensure that forest management is carried out sustainably and positively impacts the quality of land cover and economic and social aspects in the social forestry permit area.